Changes in Inflammation but Not in T-Cell Activation Precede Non-AIDS-Defining Events in a Case-Control Study of Patients on Long-term Antiretroviral Therapy. (22nd November 2017) - Angelidou, Konstantia; Hunt, Peter W; Landay, Alan L; Wilson, Cara C; Rodriguez, Benigno; Deeks, Steven G; Bosch, Ronald J; Lederman, Michael M
Abstract : In an AIDS Clinical Trials Group nested case-control study, inflammation increased prior to non-AIDS events in treated HIV-infected adults. Abstract: Background: We examined changes in soluble inflammatory cytokines and T-cell activation after antiretroviral therapy (ART) initiation in an AIDS Clinical Trials Group (ACTG) nested case-control study. Methods: Cases were 143 human immunodeficiency virus (HIV)–infected adults who developed a non-AIDS event; 315 controls remained event-free. Specimens were tested pre-ART, year 1 post-ART, and at the visit preceding the event. Conditional logistic regression evaluated the associations of biomarker changes with non-AIDS events. Results: Inflammatory and most activation biomarkers declined from pre-ART to year 1 for cases and controls. Subsequently, inflammatory biomarkers remained mostly stable in controls but not cases. Cellular activation markers generally declined for both cases and controls between year 1 and the pre-event sampling. Controls with greater pre-ART RNA levels or lower CD4 + levels had higher biomarker levels while also experiencing greater biomarker declines in the first year of ART. Changes in biomarkers to year 1 showed no significant associations with non-AIDS events. Cases, however, had significantly greater increases in all plasma biomarkers (but not cellular activation) from year 1 to the visit preceding the event. Conclusions: Inflammation increases prior to non-AIDS events in treated HIV-infected adults. These biomarker changes may reflect subclinical disease processes or other alterations in the inflammatory environment that causally contribute to disease. Clinical Trials Registration: NCT00001137.